PENGARUH MEDIA IKLAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC MAREK HONDA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Nadia Rista (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
The purpose of this study is to examine the effect of (1) advertising media on purchase decision matic brand Honda motorcycles at Faculty of Economics, University of Padang, (2) sales promotion on purchase decision matic brand Honda motorcycles at Faculty of Economics, University of Padang, (3) media advertising and sales promotion on purchase decision matic brand Honda motorcycles at Faculty of Economics, University of Padang. This type of research is to be causative by using purposive sampling techniq with a sample of 97 collect students. The results shows that (1) advertising media significantly influence the purchase decision matic brand Honda motorcycles at Faculty of Economics, University of Padang, (2) sales promotion significantly influence the purchase decision matic brand Honda motorcycles at Faculty of Economics, University of Padang, (3) advertising media and sales promotion together significantly influence the purchase decision matic brand Honda motorcycles at Faculty of Economics, University of Padang.